Demotivation Of AFL Students In The Online Learning - Muassomah Muassomah (Ijaz Arabi Journal of Arabic Learning, 2023)
Technology, which has been believed to ease and maximize a learning process, has resulted in demotivation among AFL (Arabic as a Foreign Language) students with online learning during the COVID-19 pandemic. The current research aims to map out the forms of demotivation among AFL students, analyze the factors, and show the implications on student learning outcomes. It employs a qualitative method with a narrative approach that relies on the results of interviews with students and data from student evaluations. The finding reveals that the lack of student participation indicates demotivation among AFL students during the learning process. Four factors were affecting the downturn: infrastructure, structure, partner, and teacher. This study suggests further studies to discover ways to deal with demotivation so that they are more enthusiastic about online learning.